2018
DOI: 10.1016/j.ygyno.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

GOG 244, the lymphedema and gynecologic cancer (LEG) study: Incidence and risk factors in newly diagnosed patients

Abstract: Objectives: To evaluate the incidence and risk factors for lymphedema associated with surgery for gynecologic malignancies on GOG study 244.Methods: Women undergoing a lymph node dissection for endometrial, cervical, or vulvar cancer were eligible for enrollment. Leg volume was calculated from measurements at 10-cm intervals starting 10 cm above the bottom of the heel to the inguinal crease. Measurements were obtained preoperatively and postoperatively at 4-6 weeks, and at 3-, 6-, 9-, 12-, 18-, and 24months. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…17 Data from the randomized, prospective multicenter study (SENTICOL-II) demonstrated a reduction in surgical and postoperative morbidity associated with sentinel lymph node biopsy compared with comprehensive lymphadenectomy in patients with cervical cancer. GOG 244, the lymphedema and gynecologic cancer (LEG) study, reported a lymphedema rate of 34% in 733 patients with endometrial cancer who underwent a lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Data from the randomized, prospective multicenter study (SENTICOL-II) demonstrated a reduction in surgical and postoperative morbidity associated with sentinel lymph node biopsy compared with comprehensive lymphadenectomy in patients with cervical cancer. GOG 244, the lymphedema and gynecologic cancer (LEG) study, reported a lymphedema rate of 34% in 733 patients with endometrial cancer who underwent a lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…GOG 244, the lymphedema and gynecologic cancer (LEG) study, reported a lymphedema rate of 34% in 733 patients with endometrial cancer who underwent a lymph node dissection. 17 Data from the randomized, prospective multicenter study (SENTICOL-II) demonstrated a reduction in surgical and postoperative morbidity associated with sentinel lymph node biopsy compared with comprehensive lymphadenectomy in patients with cervical cancer. 18 However, to the best of our knowledge, there is not yet similar highquality evidence establishing the incidence of morbidity after sentinel lymph node biopsy in patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies comparing patient-reported outcomes to objective metrics are still needed 13. The Gynecologic Oncology Group study 244 (GOG 244), also known as the Lymphedema and Gynecologic (LEG) cancer study, is a prospective multicenter trial which examines both objective measurement and patient-reported surveys to better our understanding of the true burden of lymphedema in patients with gynecologic malignancy 19…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…Comprehensive lymphadenectomy can result in significant chronic long‐term leg edema impairing patients' quality of life . Efforts has been made to limit the extent of nodal dissection to minimize long‐term lymphedema side effects by the application of sentinel lymph node (SLN) mapping algorithm with success .…”
Section: Introductionmentioning
confidence: 99%